Hubungan Penguasaan Materi dan Hasil Praktik Draping di Universitas PGRI Adi Buana Surabaya (International Forum of Researchers and Lecturers, 2025)
This study examines the relationship between material mastery and draping practice outcomes among students in the Family Welfare Vocational Education (PVKK) Fashion Design Study Program at PGRI Adi Buana University, Surabaya. Draping, as a technique for making patterns directly on a mannequin or the human body, is an important course in fashion design synchronization. This technique allows students to develop creativity, understand the proportions, shapes, and volumes of fabric, and produce unique works that suit the curves of the body. This study used a quantitative approach by collecting data from 60 student respondents from the 2021 and 2022 intakes through questionnaires and documentation. The variables studied were draping material mastery (independent variable) and draping practice outcomes (dependent variable). The analysis results showed a significant and positive relationship between material mastery and draping practice outcomes. The better the material mastery, the better the students' draping practice outcomes. This emphasizes that a strong theoretical understanding is an important foundation for practical skills, and learning theory and practice must be balanced to optimally improve the quality of student work. These findings have important implications for curriculum development and learning methods in the PVKK Fashion Design Study Program. To support the achievement of optimal practical results, teaching strategies are needed that integrate theory and practice in a more interactive and applicable way. For example, the use of video tutorial-based learning media, digital draping simulations, or project-based learning can strengthen students' understanding while improving their technical skills. Furthermore, increasing the intensity of practice with direct feedback from lecturers has also proven effective in accelerating technical mastery. With a holistic and adaptive learning approach, vocational education institutions can produce graduates who are not only technically competent but also competent.